2017
DOI: 10.1017/jfm.2017.154
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of multiple-bubble behaviour and induced pressure in a megasonic field

Abstract: Clarifying the mechanism of particle removal by megasonic cleaning and multiple-bubble dynamics in megasonic fields is essential for removing contaminant particles during nanodevice cleaning without pattern damage. In particular, the effect of the interaction of multiple bubbles on bubble-collapse behaviour and impulsive pressure induced by bubble collapse should also be discussed. In this study, a compressible locally homogeneous model of a gas–liquid two-phase medium is used to numerically analyse the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…In most realistic circumstances, bubble dynamic behaviours are inevitably affected by boundary conditions of the flow field or external force fields such as gravity and acoustic waves (Lauterborn & Kurz 2010;Supponen et al 2016). Up to now many experimental, numerical and theoretical studies have been carried out of bubble dynamics near different boundaries, the most commonly seen of which are rigid walls (Blake, Taib & Doherty 1986;Zhang, Duncan & Chahine 1993;Hsiao et al 2014;Wang 2014;Beig, Aboulhasanzadeh & Johnsen 2018), free surfaces (Chahine 1977;Wang et al 1996;Quah et al 2018;Kang & Cho 2019), elastic membranes (Sankin, Yuan & Zhong 2010), suspended structures (Goh et al 2017;Wu et al 2017;Li et al 2019a), adjacent bubbles (Tomita, Shima & Ohno 1984;Bremond et al 2006;Ochiai & Ishimoto 2017), etc. A significant diversity of bubble collapse patterns and jetting behaviours has been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…In most realistic circumstances, bubble dynamic behaviours are inevitably affected by boundary conditions of the flow field or external force fields such as gravity and acoustic waves (Lauterborn & Kurz 2010;Supponen et al 2016). Up to now many experimental, numerical and theoretical studies have been carried out of bubble dynamics near different boundaries, the most commonly seen of which are rigid walls (Blake, Taib & Doherty 1986;Zhang, Duncan & Chahine 1993;Hsiao et al 2014;Wang 2014;Beig, Aboulhasanzadeh & Johnsen 2018), free surfaces (Chahine 1977;Wang et al 1996;Quah et al 2018;Kang & Cho 2019), elastic membranes (Sankin, Yuan & Zhong 2010), suspended structures (Goh et al 2017;Wu et al 2017;Li et al 2019a), adjacent bubbles (Tomita, Shima & Ohno 1984;Bremond et al 2006;Ochiai & Ishimoto 2017), etc. A significant diversity of bubble collapse patterns and jetting behaviours has been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the development of the three jets makes the mesh highly distorted and irregular, so the calculation stop before 3.39ms, which causes the slight discrepancies in bubble shapes in the final collapse phase between the experiment and the simulation. The formation of one oblique jet during bubble collapse can be observed in other configurations (Brujan et al, 2018;Cui et al, 2016a;Li and Ni, 2016;Liu et al, 2016;Ochiai and Ishimoto, 2017;Rosselló et al, 2018;Tagawa and Peters, 2018), however, multiple oblique jets are rarely reported before.…”
Section: Three-dimensional Configurationmentioning
confidence: 92%
“…In natural world, multibubble interaction is more commonly seen in the above mentioned applications. If there exists another bubble nearby, one bubble alters the ambient pressure field for the other bubble, which can significantly change the bubble dynamics and increase the bubble oscillation period (Bremond et al, 2006a;Cui et al, 2016a;Han et al, 2018;Ochiai and Ishimoto, 2017). On the contrary, the bubble period is shortened due to the existence of a free surface (Wang et al, 1996b).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the studies mentioned above deal with the behavior of single bubbles, others are concerned with the practical application of multiple bubbles in the clinical domain. Several experimental 27,28 and theoretical studies [29][30][31][32][33] have investigated the stress induced by trains or clouds of multiple bubbles. (See Appendix Table III for a summary of their results.)…”
Section: Introductionmentioning
confidence: 99%